Development of stand growth scenarios based on the relationship among the crown composition, the crown structure and the productivity of Tectona grandis and Bombacopsis quinata plantations in Costa Rica - Pérez Cordero, Luis D. (1998)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1998